Bayer red mud semi-dry alkali thermal activation method and application of Bayer red mud semi-dry alkali thermal activation method in gel material
The semi-dry alkali thermal activation method enhances the alkali-activated reaction activity of Bayer red mud by adding a NaOH solution and heat treatment, improving Si and Al leaching and achieving high-strength geopolymer gel materials without additional materials.
Patent Information
- Application Number
- CN202411292355.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-14
- Publication Date
- 2024-12-17
AI Technical Summary
The low reactivity and limited utilization of Bayer red mud in alkali-activated gelling materials due to its low calcium content, high iron content, and high alkali content, leading to a low activation effect and the need for additional active materials to achieve good strength performance.
A semi-dry alkali thermal activation method involving the addition of a NaOH solution to Bayer red mud, forming a semi-dry material, pressing it into flakes, and subjecting it to heat treatment followed by grinding, which enhances the alkali-activated reaction activity.
Significantly improves the leaching capacity of Si and Al components, resulting in a geopolymer gel material with enhanced strength performance without additional active precursors, promoting large-scale utilization of Bayer red mud in gel materials.
Smart Images

Figure CN119143410A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of harmless treatment of red mud, and specifically relates to a method for semi-dry alkali thermal activation of Bayer red mud and application thereof in gel materials. Background Art
[0002] Red mud is the solid waste residue produced by the alumina industry. It is a large-scale industrial solid waste with large emissions, serious environmental impacts, and difficulty in large-scale resource utilization. At present, the global cumulative stock of red mud exceeds 5 billion tons, and it is still growing at a rate of 200 million tons per year. China is currently the world's largest producer of alumina and the largest producer of red mud. The annual output of red mud accounts for more than half of the world's total annual output, and the total reserves of red mud exceed 2 billion tons. More than 95% of the world's alumina is produced by the Bayer process, so Bayer red mud is the absolute main type of red mud. However, compared with sintering and combined red mud, the characteristics of Bayer red mud with low calcium content, high iron content, high alkali content, and low reactivity make it difficult to dispose and comprehensively utilize. Its comprehensive utilization has always been a global problem; the current utilization rate of red mud is extremely low, only about 10%.
[0003] In order to effectively improve the utilization rate of red mud and promote its large-scale consumption in the field of alkali-activated gelling material preparation, there are activation methods including direct thermal activation and alkali thermal activation to improve the alkali-activated reaction activity of red mud. Among them, the alkali thermal activation method, such as patent No. 201410160376.9, discloses a method and product for producing geopolymer gelling material from red mud. The method comprises the following steps: (1) uniformly mixing red mud with alkali metal hydroxide or carbonate, wherein the alkali metal hydroxide or carbonate added to each kilogram of red mud contains 3 to 5 moles of alkali metal elements; (2) calcining the mixture at 700°C to 900°C for 1 to 3 hours, and cooling to obtain alkali-activated red mud; (3) mixing the activated red mud with granulated blast furnace slag powder in a mass ratio of 1.5:1 to 4:1. The geopolymer gelling material produced according to the above method is uniformly mixed with water in a mass ratio of 60% to 70% when used, and cured and formed. The method uses a large amount of waste red mud from the Bayer process for producing alumina, which is environmentally friendly and low in cost. The product can be directly stirred by adding water when in use, without adding alkaline activators such as water glass, and does not need to be autoclaved or dried for forming. It is easy to use and has good adaptability. However, the activation effect of the above method needs to be improved. When using the obtained activated red mud to prepare a cementitious material, it is still often necessary to add a large proportion of additional active materials to obtain a red mud-based alkali-activated cementitious material product with good strength performance, which limits the actual utilization of red mud. Summary of the invention
[0004] The present invention aims to solve at least one of the technical problems in the related art to a certain extent. To this end, the main purpose of the present invention is to provide a Bayer red mud semi-dry alkali thermal activation method, which aims to solve the problem of low activity of activated red mud obtained by the existing Bayer red mud activation method. The present invention also provides the use of semi-dry alkali-activated red mud prepared by the Bayer red mud semi-dry alkali thermal activation method in a gel material.
[0005] The objective of the present invention is achieved through the following technical solutions:
[0006] A Bayer red mud semi-dry alkali thermal activation method comprises the following steps:
[0007] 1) adding NaOH solution to the red mud raw material, mixing evenly to form a semi-dry material, and then pressing the semi-dry material into regular flakes to obtain a flake material;
[0008] 2) The flaky material obtained in step 1) is subjected to heat treatment, and then the activated flaky material cooled to room temperature is ground and sieved to obtain semi-dry alkali-activated red mud.
[0009] In some specific embodiments, the red mud raw material is Bayer red mud.
[0010] Furthermore, the red mud raw material is low-calcium, high-iron, high-alkali Bayer red mud with low reactivity;
[0011] Furthermore, the Bayer process red mud is obtained according to the following method: the Bayer red mud waste taken from the factory is placed in an oven at 105° C. for 24 hours for drying, and then the dried blocks are crushed to form red mud raw materials.
[0012] In some specific embodiments, the NaOH solution is prepared by the following preparation method: NaOH particles having a mass ratio of Na2O to red mud raw material of (10-15):100 are dissolved in a certain mass of deionized water, and the solution is cooled to room temperature and then fixed to volume.
[0013] In some specific embodiments, the mass ratio of the NaOH solution to the red mud raw material is controlled to be 0.1-0.5 mL / g.
[0014] Furthermore, the NaOH solution and the red mud raw material are added at a ratio of 0.25 mL / g and mixed evenly to form a semi-dry material.
[0015] In some specific embodiments, the process parameters of the heat treatment are: temperature of 600-900° C. and time of 1-3 h.
[0016] Furthermore, the process parameters of the heat treatment are: temperature of 700-900°C and time of 1-2h.
[0017] The present invention also aims to provide a semi-dry alkali-activated red mud.
[0018] The present invention also aims to provide a geopolymer gel material, which comprises the aforementioned semi-dry alkali thermally activated red mud.
[0019] In some specific embodiments, the semi-dry alkali heat-activated red mud is activated by sodium silicate solution, and the liquid-to-cement ratio is controlled to 0.4, the ash-sand ratio is controlled to 1:2, and the mixture is evenly mixed to form mortar, which is poured into a mold and vibrated to prepare a sample. After 24 hours, the material is demolded and cured to obtain a geopolymer gel material.
[0020] Compared with the prior art, the present invention has at least the following advantages:
[0021] 1) The Bayer red mud semi-dry alkali thermal activation method provided by the present invention is to add a certain proportion of NaOH solution to the red mud raw material instead of the traditional addition of solid NaOH particles, to form a semi-dry material, press it into sheets, and then calcine, activate and grind it to obtain semi-dry alkali-activated red mud; at the same activation temperature and the same NaOH dosage, the leaching ability of Si and Al components in the semi-dry alkali-activated red mud in alkali solution is significantly improved compared with direct thermal activation and traditional alkali thermal activation, that is, the alkali-activated reaction activity is significantly improved;
[0022] 2) The geopolymer gel material provided by the present invention, without adding additional active precursors, adopts 100% semi-dry alkali-activated red mud, and is prepared by 2.5 modulus water glass excitation under normal temperature curing conditions of 20±2°C. The 7-day strength of the geopolymer gel material can reach 31.72MPa; it vigorously promotes the large-scale utilization of Bayer red mud in the field of gel material preparation, and provides technical support for the industry to provide green geopolymer gel materials with excellent performance. BRIEF DESCRIPTION OF THE DRAWINGS
[0023] In order to more clearly illustrate the specific implementation of the present invention, the drawings required for use in the specific implementation or the description of the prior art will be briefly introduced below.
[0024] Figure 1 is the Si leaching concentration in the activated red mud and the red mud raw material in each embodiment and comparative example;
[0025] Figure 2 is the Al leaching concentration in the activated red mud and the red mud raw material in each embodiment and comparative example;
[0026] Figure 3 is the compressive strength of the geopolymer prepared from the activated red mud in each example and comparative example;
[0027] Figure 4 The XRD spectra of the activated red mud and the red mud raw material obtained in Example 4 and Comparative Example 4;
[0028] Figure 5 These are the morphologies of the semi-dry alkali thermally activated red mud of Example 4 and the alkali thermally activated red mud of Comparative Example 4 and their geopolymers. DETAILED DESCRIPTION
[0029] The present invention will be further described in detail below in conjunction with the accompanying drawings and embodiments. The following embodiments are only illustrative and not restrictive, and the protection scope of the present invention cannot be limited thereto.
[0030] When a certain amount, concentration or other value or parameter is expressed in the form of a range, a preferred range, or a preferred upper and lower numerical limit, it should be understood that it is equivalent to specifically revealing any range by combining any pair of upper range limits or preferred numerical values with any lower range limit or preferred numerical value, regardless of whether the range is specifically disclosed. Unless otherwise indicated, the numerical range values listed herein include the endpoints of the range, and all integers and fractions within the range.
[0031] Unless otherwise indicated, all percentages, parts, ratios, etc. herein are by weight.
[0032] The materials, methods, and examples herein are illustrative and are not to be construed as limiting unless specifically stated.
[0033] In the following embodiments, the Bayer red mud raw material was purchased from Shandong Zibo Alumina Production Company, and its main components were 24.29% SiO2, 20.83% Al2O3, 1.40% CaO, 32.06% Fe2O3, 5.94% Na2O, 4.19% TiO2, 0.22% K2O, 0.05% MgO, 0.43% P2O5, 0.47% SO3, 0.08% Cl, and 9.68% loss on ignition.
[0034] Example 1
[0035] This embodiment provides a method for semi-dry alkali thermal activation of Bayer red mud, comprising the following steps:
[0036] 1) The red mud waste from the factory is placed in an oven and dried at 105°C overnight for 24 hours, and then the dried blocks are crushed to form red mud raw materials;
[0037] 2) Weigh 15 g of NaOH pellets containing Na2O, dissolve them in a certain amount of deionized water, and after the solution is cooled to room temperature, dilute to 25 mL to prepare a NaOH solution;
[0038] 3) Pour 25 ml of the NaOH solution prepared in step 2) into 100 g of the red mud raw material, mix evenly to form a semi-dry material, and then use a mold to press the semi-dry material into regular sheets;
[0039] 4) The flaky material is placed in a crucible and placed in a muffle furnace for calcination at 600° C. for 2 h at a heating rate of 10° C. / min. The activated flaky material cooled to room temperature is then ground through a 200-mesh sieve to obtain semi-dry alkali thermally activated red mud.
[0040] Example 2
[0041] The difference from Example 1 is that the activation temperature is changed to 700° C. The Bayer red mud semi-dry alkali thermal activation method of this embodiment comprises the following steps:
[0042] 1) The red mud waste from the factory is placed in an oven and dried at 105°C overnight for 24 hours, and then the dried blocks are crushed to form red mud raw materials;
[0043] 2) Weigh 15 g of NaOH pellets containing Na2O, dissolve them in a certain amount of deionized water, and after the solution is cooled to room temperature, dilute to 25 mL to prepare a NaOH solution;
[0044] 3) Pour 25 ml of the NaOH solution prepared in step 2) into 100 g of the red mud raw material, mix evenly to form a semi-dry material, and then use a mold to press the semi-dry material into regular sheets;
[0045] 4) The flaky material is placed in a crucible and placed in a muffle furnace for calcination at 700° C. for 2 h at a heating rate of 10° C. / min. The activated flaky material cooled to room temperature is then ground into powder to obtain semi-dry alkali thermally activated red mud.
[0046] Example 3
[0047] The difference from Example 2 is that the activation temperature is changed to 800° C. This example provides a Bayer red mud semi-dry alkali thermal activation method, comprising the following steps:
[0048] 1) The red mud waste from the factory is placed in an oven and dried at 105°C overnight for 24 hours, and then the dried blocks are crushed to form red mud raw materials;
[0049] 2) Weigh 15 g of NaOH pellets containing Na2O, dissolve them in a certain amount of deionized water, and after the solution is cooled to room temperature, dilute to 25 mL to prepare a NaOH solution;
[0050] 3) Pour 25 ml of the NaOH solution prepared in step 2) into 100 g of the red mud raw material, mix evenly to form a semi-dry material, and then use a mold to press the semi-dry material into regular sheets;
[0051] 4) The flaky material is placed in a crucible and placed in a muffle furnace for calcination at 800° C. for 2 h at a heating rate of 10° C. / min. The activated flaky material cooled to room temperature is then ground into powder to obtain semi-dry alkali thermally activated red mud.
[0052] Example 4
[0053] The difference from Example 3 is that the activation temperature is changed to 900° C. This example provides a Bayer red mud semi-dry alkali thermal activation method, comprising the following steps:
[0054] 1) The red mud waste from the factory is placed in an oven and dried at 105°C overnight for 24 hours, and then the dried blocks are crushed to form red mud raw materials;
[0055] 2) Weigh 15 g of NaOH pellets containing Na2O, dissolve them in a certain amount of deionized water, and after the solution is cooled to room temperature, dilute to 25 mL to prepare a NaOH solution;
[0056] 3) Pour 25 ml of the NaOH solution prepared in step 2) into 100 g of the red mud raw material, mix evenly to form a semi-dry material, and then use a mold to press the semi-dry material into regular sheets;
[0057] 4) The flaky material is placed in a crucible and placed in a muffle furnace for calcination at 900° C. for 2 h at a heating rate of 10° C. / min. The activated flaky material cooled to room temperature is then ground into powder to obtain semi-dry alkali thermally activated red mud.
[0058] Example 5
[0059] The difference from Example 4 is that the mass of Na2O added in the preparation of the NaOH solution is changed to 10 g. This example provides a method for semi-dry alkali thermal activation of Bayer red mud, comprising the following steps:
[0060] 1) The red mud waste from the factory is placed in an oven and dried at 105°C overnight for 24 hours, and then the dried blocks are crushed to form red mud raw materials;
[0061] 2) Weigh 10 g of NaOH pellets containing Na2O, dissolve them in a certain amount of deionized water, and after the solution is cooled to room temperature, dilute to 25 mL to prepare a NaOH solution;
[0062] 3) Pour 25 ml of the NaOH solution prepared in step 2) into 100 g of the red mud raw material, mix evenly to form a semi-dry material, and then use a mold to press the semi-dry material into regular sheets;
[0063] 4) The flaky material is placed in a crucible and placed in a muffle furnace for calcination at 900° C. for 2 h at a heating rate of 10° C. / min. The activated flaky material cooled to room temperature is then ground into powder to obtain semi-dry alkali thermally activated red mud.
[0064] Comparative Example 1
[0065] The difference from Example 1 is that an equal amount of NaOH solid particles is used instead of NaOH solution to uniformly mix with the red mud raw material and then calcine and activate to obtain alkali-heat activated red mud. The steps include:
[0066] 1) The red mud waste from the factory is placed in an oven and dried at 105°C overnight for 24 hours, and then the dried blocks are crushed to form red mud raw materials;
[0067] 2) Weigh 15 g of NaOH pellets containing Na2O and 100 g of red mud raw material, pour the NaOH pellets into the red mud raw material, and mix them evenly;
[0068] 3) The material is placed in a crucible and placed in a muffle furnace for calcination at 600° C. for 2 h at a heating rate of 10° C. / min. The activated material cooled to room temperature is then ground into powder to obtain alkali-thermally activated red mud.
[0069] Comparative Example 2
[0070] The difference from Example 2 is that an equal amount of NaOH solid particles is used instead of NaOH solution to uniformly mix with the red mud raw material and then calcine and activate to obtain alkali-heat activated red mud. The steps include:
[0071] 1) The red mud waste from the factory is placed in an oven and dried at 105°C overnight for 24 hours, and then the dried blocks are crushed to form red mud raw materials;
[0072] 2) Weigh 15 g of NaOH pellets containing Na2O and 100 g of red mud raw material, pour the NaOH pellets into the red mud raw material, and mix them evenly;
[0073] 4) The material is placed in a crucible and placed in a muffle furnace for calcination at 700° C. for 2 h at a heating rate of 10° C. / min. The activated material cooled to room temperature is then ground into powder to obtain alkali-thermally activated red mud.
[0074] Comparative Example 3
[0075] The difference from Example 3 is that an equal amount of NaOH solid particles is used instead of NaOH solution to uniformly mix with the red mud raw material and then calcine and activate to obtain alkali-heat activated red mud. The steps include:
[0076] 1) The red mud waste from the factory is placed in an oven and dried at 105°C overnight for 24 hours, and then the dried blocks are crushed to form red mud raw materials;
[0077] 2) Weigh 15 g of NaOH pellets containing Na2O and 100 g of red mud raw material, pour the NaOH pellets into the red mud raw material, and mix them evenly;
[0078] 4) The material is placed in a crucible and placed in a muffle furnace for calcination at 800° C. for 2 h at a heating rate of 10° C. / min. The activated material cooled to room temperature is then ground into powder to obtain alkali-thermally activated red mud.
[0079] Comparative Example 4
[0080] The difference from Example 4 is that an equal amount of NaOH solid particles is used instead of NaOH solution to uniformly mix with the red mud raw material and then calcine and activate to obtain alkali-heat activated red mud. The steps include:
[0081] 1) The red mud waste from the factory is placed in an oven and dried at 105°C overnight for 24 hours, and then the dried blocks are crushed to form red mud raw materials;
[0082] 2) Weigh 15 g of NaOH pellets containing Na2O and 100 g of red mud raw material, pour the NaOH pellets into the red mud raw material, and mix them evenly;
[0083] 4) The material is placed in a crucible and placed in a muffle furnace for calcination at 900° C. for 2 h at a heating rate of 10° C. / min. The activated material cooled to room temperature is then ground into powder to obtain alkali-thermally activated red mud.
[0084] Comparative Example 5
[0085] The difference from Example 5 is that an equal amount of NaOH solid particles is used instead of NaOH solution to uniformly mix with the red mud raw material and then calcine and activate to obtain alkali-heat activated red mud. The steps include:
[0086] 1) The red mud waste from the factory is placed in an oven and dried at 105°C overnight for 24 hours, and then the dried blocks are crushed to form red mud raw materials;
[0087] 2) Weighing NaOH pellets containing 10 g of Na2O and 100 g of red mud raw material, pouring the NaOH pellets into the red mud raw material and mixing them evenly;
[0088] 4) The material is placed in a crucible and placed in a muffle furnace for calcination at 900° C. for 2 h at a heating rate of 10° C. / min. The activated material cooled to room temperature is then ground into powder to obtain alkali-thermally activated red mud.
[0089] Performance Testing
[0090] The present application tests the activated red mud prepared in Examples 1-5 and Comparative Examples 1-5 respectively to demonstrate the alkali-activated activity of the activated red mud; the main properties tested in the present application include the leaching capacity of Si and Al components in the activated red mud, the compressive strength of the activated red mud-based polymer gel material, and the physical phase test of the activated red mud. The specific testing method is as follows:
[0091] 1) Test on Si and Al leaching performance in activated red mud
[0092] Take a certain amount of activated red mud from each embodiment and comparative example into an extraction bottle, calculate and add the required volume of 8mol / L NaOH solution according to the solid-liquid ratio of 1:20g / mL, cover the bottle cap tightly and fix it on the flip-type oscillating device, adjust the speed to 30±2r / min, and oscillate at 23±2℃ for 18±2h. The obtained leachate is filtered, diluted, acidified, and then the Si and Al concentrations are detected by ICP-OES;
[0093] 2) Compressive strength test of geopolymer gel material
[0094] The activated red mud prepared in each embodiment or comparative example is stimulated with a 2.5 modulus sodium silicate solution, and the liquid-to-cement ratio is controlled to be 0.4, and the ash-sand ratio is controlled to be 1:2, and the mixture is evenly mixed to form mortar, the mortar is poured into a mold, and vibrated to prepare a sample. After 24 hours, the sample is demolded and cured under standard conditions of 20±2°C and relative humidity>95% to obtain a geopolymer gel material; after the curing is completed, a compressive strength test is performed using a universal testing machine.
[0095] 3) Activated red mud phase test
[0096] The phase analysis of activated red mud was carried out by Rigaku SmartLab X-ray diffractometer (XRD).
[0097] The specific test results are shown in Table 1. Figure 1 , Figure 2 and Figure 3 As shown, specifically:
[0098] Table 1 Properties of activated red mud and its geopolymer in various examples and comparative examples
[0099] Si leaching concentration (mg / L) Al leaching concentration (mg / L) Compressive strength(MPa) Example 1 1432.5 3251.3 6.16 Example 2 2272.2 2815.7 15.82 Example 3 2661.4 2723.7 18.27 Example 4 3340.1 3175.3 31.72 Example 5 2198.4 2118.0 20.01 Comparative Example 1 935.2 1618.7 1.32 Comparative Example 2 1500.1 1996.2 8.18 Comparative Example 3 2014.7 2350.9 8.68 Comparative Example 4 2057.1 2070.8 16.42 Comparative Example 5 1539.5 1572.3 11.78
[0100] 1) Si and Al leaching test in activated red mud
[0101] As can be seen from Table 1, at the same activation temperature and NaOH dosage, the semi-dry alkali thermal activation method proposed in this application has a more significant effect on improving the alkali activation activity of Bayer red mud than the traditional alkali thermal activation method. For example, the Si leaching concentration in the semi-dry alkali thermal activated red mud in Example 4 reached a maximum value of 3340.1 mg / L, which was 62.4% higher than the maximum Si leaching concentration of 2057.1 mg / L in the traditional alkali thermal activated red mud in Comparative Example 4, and 422.6% higher than the RM raw material (639.1 mg / L). At the same time, the Al leaching concentration reached 3175.3 mg / L, which was 53.3% higher than the Al leaching concentration of 2070.8 mg / L in the traditional alkali thermal method, and 228.2% higher than the RM raw material (964.7 mg / L).
[0102] It can be seen that the Bayer red mud semi-dry alkali thermal activation method proposed in the present application, by adopting the method of adding alkali solution instead of the traditional method of adding solid alkali, combined with thermal activation at a specific temperature, can effectively improve the Si and Al leaching capacity in the semi-dry alkali thermally activated red mud, significantly improve the alkali activation activity of the Bayer red mud, and thereby increase the dosage of the Bayer red mud in the preparation of gel materials with excellent strength properties.
[0103] 2) Strength performance test of geopolymer gel material
[0104] As shown in Table 1, under the same conditions, the strength of the geopolymer gel material prepared from 100% semi-dry alkali-heat activated red mud in Examples 1-5 is significantly improved compared with the traditional alkali-heat activated red mud foundation in Comparative Examples 1-5. Among them, the geopolymer mortar prepared by 2.5 modulus water glass activation using 15% Na2O dosage + 900°C calcination activation (Example 4) can reach 31.72MPa in 7 days under normal temperature curing conditions of 20±2°C, which is 93.2% higher than the geopolymer mortar strength of 16.42MPa prepared from the traditional alkali-heat activated red mud under the same conditions.
[0105] 3) XRD test
[0106] This application takes Example 4 and Comparative Example 4 as examples, and performs XRD test on the prepared activated red mud. The results are as follows Figure 4 As shown. Figure 4 It can be seen that, compared with Comparative Example 4, Example 4 more effectively converts the quartz (2θ=26.622°), boehmite (2θ=14.388°), gibbsite (2θ=18.158°) and other phases in the red mud raw material into phases soluble in alkali solution, specifically, more alkali-soluble triclinic pyroxene (2θ=20.860°), sodium-rich triclinic pyroxene (2θ=34.878°), low-crystallinity jadeite (2θ=31.578°), and active amorphous amorphous aluminosilicates mainly located at 2θ=32-37° and other dispersed locations are generated, reflecting the physical phase mechanism that the semi-dry alkali-heat-activated red mud obtained by Example 4 has a significant activity advantage over Comparative Example 4.
[0107] The actual pictures of the activated red mud and the geopolymer gel material prepared therefrom in Example 4 and Comparative Example 4 of the present application are as follows: Figure 5 shown.
[0108] In summary, the semi-dry alkali thermal activation method proposed in this application can significantly improve the leaching capacity of Si and Al in Bayer red mud, that is, significantly improve the alkali activation activity of Bayer red mud. Moreover, without adding other materials, the strength of the geopolymer mortar made from 100% semi-dry alkali thermal activated red mud can reach 30MPa, which is nearly double that of the traditional alkali thermal method under the same conditions.
[0109] The above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein by equivalents. These modifications or replacements do not make the essence of the corresponding technical solutions deviate from the scope of the technical solutions of the embodiments of the present invention, and they should all be included in the scope of the claims and specification of the present invention.
Claims
1. A Bayer red mud semi-dry alkali thermal activation method, characterized in that: The steps include: 1) adding NaOH solution to the red mud raw material, mixing evenly to form a semi-dry material, and then pressing the semi-dry material into regular flakes to obtain a flake material; 2) The flaky material obtained in step 1) is subjected to heat treatment, and then the activated flaky material cooled to room temperature is ground and sieved to obtain semi-dry alkali-activated red mud.
2. The Bayer red mud semi-dry alkali thermal activation method according to claim 1, characterized in that: The red mud raw material is Bayer red mud.
3. The Bayer red mud semi-dry alkali thermal activation method according to claim 1, characterized in that: The NaOH solution and the red mud raw material are added in a ratio of 0.1-0.5 mL / g and mixed evenly to form a semi-dry material.
4. The Bayer red mud semi-dry alkali thermal activation method according to claim 3, characterized in that: The mass ratio of Na2O contained in the NaOH solution to the red mud raw material is (10-15):
100.
5. The Bayer red mud semi-dry alkali thermal activation method according to claim 1, characterized in that: The process parameters of the heat treatment are: temperature of 600-900° C. and time of 1-3 h.
6. A semi-dry alkali-activated red mud, characterized in that: The semi-dry alkali-activated red mud is prepared by the activation method described in any one of claims 1-7.
7. A geopolymer gel material, characterized in that: It includes the semi-dry alkali thermally activated red mud described in claim 8.
8. The geopolymer gel material according to claim 7, characterized in that: The semi-dry alkali thermally activated red mud is activated by sodium silicate solution, and the liquid-to-cement ratio is controlled to be 0.4, the ash-to-sand ratio is controlled to be 1:2, and the mixture is evenly mixed to form mortar, which is then poured into a mold and vibrated to prepare a sample, and then demolded and cured after 24 hours to obtain a geopolymer gel material.
